Wybrane techniczno-technologiczne uwarunkowania rozwoju bankowości internetowej w Polsce w latach 2000-2003 (stan z lutego 2004 roku) - Kisiel, Michał (The Influence of the Technological Factors on the Development of Internet Banking in Poland Between 2000 and 2003 (State of February 2004), 2005)
The technological factors are of great importance in the development of Internet banking in Poland. In the article the main existing barriers were presented: the underdeveloped telecommunication infrastructure and the high costs of Internet access services. The technologies of authentication used by Polish internet banks as well as the innovations in this area (biometrics) were described. The article also covers the specific threats faced by banks offering the internet banking - the danger of identity theft and other forms of computer attacks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 213-233